Interactive effects of biochar and chemical fertilizer on water and nitrogen dynamics, soil properties and maize yield under different irrigation methods - Wang, Lei; Leghari, Shah Jahan; Wu, Jiajun; Wang, Na; Pang, Min; Jin, Liang (Frontiers in Plant Science, 2023)
Long-term application of nitrogen (N) fertilizer adversely degrades soil and decreases crop yield. Biochar amendment with N fertilizer not only can increase yield but also can improve the soil. A 3-year field experiment was conducted to determine the effect of biochar doses with N fertilizer on maize yield and soil N and water dynamics under border irrigation (BI) and drip irrigation (DI) methods. Treatments were 260 kg N ha−1 without biochar addition and combined with low, medium, and high doses of biochar, namely, 15.5 t ha−1, 30.7 t ha−1, and 45.3 t ha−1 (NB0, NB1, NB2, and NB3), respectively. The biochar doses and irrigation methods significantly (p < 0.05) increased maize growth and yield characteristics, irrigation water use efficiency (IWUE), and fertilizer N use efficiency (FNUE) and enhanced the soil properties. In the BI and DI method, the NB1, NB2, and NB3 treatments increased yield by 4.96%–6.10%, 8.36%–9.85%, and 9.65%–11.41%, respectively, compared to NB0. In terms of IWUE and FNUE, the non-biochar treatment had lower IWUE and FNUE compared to biochar combined with N fertilizer treatments under both BI and DI methods. In the BI method, the IWUE in NB2 and NB3 ranged from 3.36 to 3.43 kg kg−1, and in DI, it was maximum, ranging from 5.70 to 5.94 kg kg−1. Similarly, these medium and high doses of biochar increased the FNUE of maize. The FNUEs in NB2 and NB3 under BI ranged from 38.72 to 38.95 kg kg−1 and from 38.89 to 39.58 kg kg−1, while FNUEs of these same treatments under DI ranged from 48.26 to 49.58 kg kg−1 and from 48.92 to 50.28 kg kg−1. The effect of biochar was more obvious in DI as compared to the BI method because soil water content (SWC) and soil N concentrations (SNCs) were higher at rhizosphere soil layers under DI. Biochar improved SWC and SNC at 0–20 cm and 20–40 cm soil layers and decreased below 60-cm soil layers. In contrast, despite biochar-controlled SWC and SNCs, still, values of these parameters were higher in deeper soil layers. In the BI method, the SNCs were higher at 60–80 cm and 80–100 cm compared to the top and middle soil layers. Depth-wise results of SNC demonstrated that the biochar’s ability to store SNC was further enhanced in the DI method. Moreover, biochar increased soil organic matter (OM) and soil aggregate stability and maintained pH. The NB0 treatment increased soil OM by 11.11%–14.60%, NB2 by 14.29%–19.42%, and NB3 by 21.98%–23.78% in both irrigation methods. This increased OM resulted in improved average soil aggregates stability by 2.45%–11.71% and 4.52%–14.66% in the BI and DI method, respectively. The results of our study revealed that combined application of N fertilizer with a medium dose of biochar under the DI method would be the best management practice, which will significantly increase crop yield, improve SWC, enrich SNC and OM, improve soil structure, and maintain pH.